Dynamics of oil droplet impacting and wetting on the inclined surfaces with different roughness. (February 2021) - Wang, Lingzi; Feng, Jianmei; Dang, Tiendat; Peng, Xueyuan
Highlights: Experiments of the oil droplet impact on the inclined surface were performed. Phenomenological description of droplet spreading under various inclined angle and We . Effects of the surface roughness on the normalized droplet spreading. The orders of the normalized droplet spreading under various parameters. Abstract: This study experimentally investigated the wetting process of an oil droplet impacting on the dry surface with different surface roughness (0.3 μm, 1.6μm, 2.9μm, 5.2 μm) from the front view. Experiments were conducted under three impacting Weber ranges with the inclined angles of 37.0°, 63.0°, and 75.5°. The droplet spread as a 'pancake' on the surface when the inclination angle was 37.0°, while the shape of an 'avocado' of the flowing oil layer was observed on higher inclined angle surfaces. The upper part of the 'avocado' became narrower when the inclined angle increased from 63.0° to 75.5°, which then grew longer with the increase in the impact We . The normalized transverse and longitudinal spreading displacement β x and β y were defined, whose evolution with normalized time was then obtained. Three stages of the β x were divided and analyzed. Under the same We range and inclined angle, the largest value of the maximum normalized droplet transverse spreading displacement ( β x m a x ) was obtained with the smoothest surface (0.3 μm) followed by the roughest surface (5.2 μm). β x m a x was affected by the surface roughness, which also influences the contact angle of the surface. When the surface roughness and the contact angle were regarded as two separate factors, it was found that for the transverse spreading, the lower the inclined angle, the more obvious effect of the surface roughness than that of the contact angle.